2022
DOI: 10.2196/35730
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19 and Prevention Behaviors: Cross-Lagged Panel Analysis

Abstract: Background The ongoing COVID-19 pandemic has brought forth conversations about effective behavior change models for increasing prevention behavior, ranging from wearing masks in public to physical distancing. Among the considered behavior change techniques is the use of fear appeals, through which a negative possible outcome is emphasized to invoke fear, which in turn may promote prevention behaviors to counter the likelihood of the negative outcome. Although fear is hypothesized as health promotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…This finding is in line with previous studies showing that anxiety is associated with the prevention behaviors of older adults ( 7 , 48 ). However, a previous study also showed that fear did not predict prevention behavior 6 months later in US women ( 60 ), possibly because older adults have more life experiences and tend to become more cautious and inclined to have better compliance with preventive measures after experiencing negative psychological emotions ( 61 ). Moreover, the cross-lagged effect between prevention behavior in wave 1 and negative emotions in wave 2 was not significant.…”
Section: Discussionmentioning
confidence: 94%
“…This finding is in line with previous studies showing that anxiety is associated with the prevention behaviors of older adults ( 7 , 48 ). However, a previous study also showed that fear did not predict prevention behavior 6 months later in US women ( 60 ), possibly because older adults have more life experiences and tend to become more cautious and inclined to have better compliance with preventive measures after experiencing negative psychological emotions ( 61 ). Moreover, the cross-lagged effect between prevention behavior in wave 1 and negative emotions in wave 2 was not significant.…”
Section: Discussionmentioning
confidence: 94%
“…Since the beginning of the COVID-19 pandemic, numerous countries have adopted measures to contain the spread of SARS-CoV-2. The main strategies to contain the contagion were social distancing, wearing masks, and lockdown, the latter more intensely (Marson and Ortega, 2020 ; Boschiero et al, 2021 ; Anderson and Stockman, 2022 ). However, considering the current Brazilian scenario, it is observed that the behavior of people in a post-pandemic world opens a window to potential forgetfulness of what the disease is capable of, since even with the recommendations of public health specialists, Brazilians presented attitudes that challenged their own survival during the COVID-19 pandemic (Martins et al, 2023 ).…”
mentioning
confidence: 99%
“…So, wearing masks and maintaining social distancing were effective in the beginning. However, over these four years of the COVID-19 pandemic, it has been noted that people no longer adhered to protection recommendations (Anderson and Stockman, 2022 ). Have they lost their fear of possible contamination?…”
mentioning
confidence: 99%